Council Directive (EU) 2018/822 and the Right to Privacy. An Attempt to Answer the Preliminary Question in Case C-694/20 - Szymacha, Adam (Przegląd Prawniczy Uniwersytetu im. Adam Mickiewicza, 2022)
Through an action before the Court of Justice of the European Union (CJEU), the Belgian Constitutional Court intends to obtain an answer to the question related to the compatibility of Council Directive (EU) 2018/822 with the fundamental right to respect for private life. The mechanism provided by this Directive may violate this right because it consists in obliging the lawyer who has invoked the Legal Professional Privilege to provide information about the evasion of the obligation to inform the authorities about the cross-border arrangement. This arrangement may amount to tax avoidance by the client. I will try to predict the possible response of the CJEU by analyzing its previous case law. Interference with fundamental rights must be proportionate. The secrecy of the lawyer’s communication with his client deserves special protection. The proportionality of the interference may be evidenced by filters such as judicial supervision, intermediation by an independent authority etc.